Documental histórico para poner en valor la memoria oral de los pobladores de la parroquia Sicalpa del cantón Colta. - Ninabanda Pomagualli, John Carlos (2024)
This project established the development of the description of the production of a historical documentary as a tool for strengthening and revaluing the oral memory of the inhabitants of the Sicalpa parish of the Colta canton. The proposed methodology consisted of a qualitative approach, types of descriptive and exploratory research, non-experimental research design, methods: analytical-synthetic, empirical, ethnographic, projective, and whose data collection techniques corresponded to direct observation through application of observation sheet and interview, through the development of a guide of the same, through the appeal of the cultural and folkloric knowledge of the population of elderly people knowledgeable and dedicated to the motive of the detail of the roots of the parish by inheritance and vocation, selecting a total sample of three elderly people. The analysis and interpretation of qualitative data was performed using the Atlas.Ti tool, to finally develop the proposal through the phases of presenting the interview of the oral memory of Sicalpa to the cultists, developing the protocol of pre-production, production, post-production based on projective methodology and proposing promotion on social networks as an advertising instrument. Finally, it was verified the cultural division of the parish from the population segments of indigenous people and mestizos, establishing the particular characteristics and perspectives of each one of the meaning of the symbols of: gastronomy, architecture, clothing, stories and legends, music and special dates.